Wand and Weber's good decomposition conditions for BPMN. Issue 5 (26th August 2014) - Johannsen, Florian; Leist, Susanne; Tausch, Reinhold
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to specify the decomposition conditions of Wand and Weber for the Business Process Model and Notation (BPMN). Therefore, an interpretation of the conditions for BPMN is derived and compared to a specification of the conditions for enhanced Event-Driven Process Chains (eEPCs). Based on these results, guidelines for a conformance check of BPMN and eEPC models with the decomposition conditions are shown. Further, guidelines for decomposition are formulated for BPMN models. The usability of the decomposition guidelines is tested with modelling experts. Design/methodology/approach – An approach building on a representational mapping is used for specifying the decomposition conditions. Therefore, ontological constructs of the Bunge-Wand-Weber ontology are mapped to corresponding modelling constructs and an interpretation of the decomposition conditions for BPMN is derived. Guidelines for a conformance check are then defined. Based on these results, decomposition guidelines are formulated. Their usability is tested in interviews. Findings – The research shows that the decomposition conditions stemming from the information systems discipline can be transferred to business process modelling. However, the interpretation of the decomposition conditions depends on specific characteristics of a modelling language. Based on a thorough specification of the conditions, it is possible to derive guidelines for a conformance check of process models with the conditions. In addition, guidelines for decomposition are developed and tested. In the study, these are perceived as understandable and helpful by experts. Research limitations/implications – Research approaches based on representational mappings are subjected to subjectivity. However, by having three researchers performing the approach independently, subjectivity can be mitigated. Further, only ten experts participated in the usability test, which is therefore to be considered as a first step in a more comprising evaluation. Practical implications – This paper provides the process modeller with guidelines enabling a conformance check of BPMN and eEPC process models with the decomposition conditions. Further, guidelines for decomposing BPMN models are introduced. Originality/value – This paper is the first to specify Wand and Weber's decomposition conditions for process modelling with BPMN. A comparison to eEPCs shows, that the ontological expressiveness influences the interpretation of the conditions. Further, guidelines for decomposing BPMN models as well as for checking their adherence to the decomposition conditions are presented.